Theoretical study of the scalar coupling constants across the noncovalent contacts in RNA base pairs: the cis- and trans-watson-crick/sugar edge base pair family - Vokacova, Zuzana; Sponer, Jirí; Sponer, Judit E; Sychrovský, Vladimír (The journal of physical chemistry. B, 2007)
The structure and function of RNA molecules are substantially affected by non-Watson-Crick base pairs actively utilizing the 2'-hydroxyl group of ribose. Here we correlate scalar coupling constants across the noncovalent contacts calculated for the cis- and trans-WC/SE (Watson-Crick/sugar edge) RNA base pairs with the geometry of base to base and sugar to base hydrogen bond(s). 23 RNA base pairs from the 32 investigated were found in RNA crystal structures, and the calculated scalar couplings are therefore experimentally relevant with regard to the binding patterns occurring in this class of RNA base pairs. The intermolecular scalar couplings 1hJ(N,H), 2hJ(N,N), 2hJ(C,H), and 3hJ(C,N) were calculated for the N-H...N and N-H...O=C base to base contacts and various noncovalent links between the sugar hydroxyl and RNA base. Also, the intramolecular 1J(N,H) and 2J(C,H) couplings were calculated for the amino or imino group of RNA base and the ribose 2'-hydroxyl group involved in the noncovalent interactions. The calculated scalar couplings have implications for validation of local geometry, show specificity for the amino and imino groups of RNA base involved in the linkage, and can be used for discrimination between the cis- and trans-WC/SE base pairs. The RNA base pairs within an isosteric subclass of the WC/SE binding patterns can be further sorted according to the scalar couplings calculated across different local noncovalent contacts. The effect of explicit water inserted in the RNA base pairs on the magnitude of the scalar couplings was calculated, and the data for discrimination between the water-inserted and direct RNA base pairs are presented. The calculated NMR data are significant for structural interpretation of the scalar couplings in the noncanonical RNA base pairs.
Keywords: Hydrogen Bonding; Nucleosides; voda; chemické modely; Models, Molecular; Models, Chemical; magnetická rezonanční spektroskopie; párování bází; vodíková vazba; Base Pairing; Magnetic Resonance Spectroscopy; Water; molekulární modely; RNA; nukleosidy